Pandemia covid-2019: el dolor emocional como representación pictórica expresionista (de angustia, del horror, de lo grotesco de la vida - muerte) - Pasaca Chamba, Johnny Gonzalo (2022)
The present research work called Pandemic covid-2019: emotional pain as expressionist pictorial representation (of anguish, horror, the grotesque of life - death); proposes an approach of analysis of expressionism for the elaboration of a plastic proposal based on basic concepts. The expression of subjectivity, emphasizing the internal feelings of people, being the existential anguish linked to Heidegger's approach, considered as the engine of his ethics, as well as certain aesthetic categories, in this case pessimistic that go hand in hand with expressionism. The purpose of the research is to rationalize the artistic-historical processes that have occurred in art within this theme (pandemics), thus filtering the information to subsequently test in the creative processes; this based on the main application of deductive-inductive methods, which allow processing the information that goes from the general concepts to the particular ones in order to achieve a better understanding of both representation of theme and stylistic characteristics, thought or historical context linked to the expressionist movement object of study and application. In addition, observation cards are developed, which allow the collection and structuring of analysis data of referential works to be systematically written in order to contribute to the subsequent sketching process and thus have a relationship in terms of theoretical-practical work. The artistic plasticity is implemented based on the experimentation of expressionist techniques retaken in its different characterizations where the taste of reflecting a subjective world is born, objectified or materialized in the exterior in the pictorial work, without leaving aside the conscious actuated in the unconscious and the emotions, they are transparent in the work using symbolic elements that are within reach taking into account other people's or personal experiences, likewise the study of the artistic referential iconography is present whose elements allow to be integrated to the present being a fundamental pillar in the development of the work. Keywords: expression, Pandemic, expression, emotions, grotesque, experimentation, gestures.